Early symptoms in symptomatic and preclinical genetic frontotemporal lobar degeneration. Issue 9 (7th August 2020) - Tavares, Tamara Paulo; Mitchell, Derek G V; Coleman, Kristy KL; Coleman, Brenda L; Shoesmith, Christen L; Butler, Christopher R; Santana, Isabel; Danek, Adrian; Gerhard, Alexander; de Mendonca, Alexandre; Borroni, Barbara; Tartaglia, Maria Carmela; et al.
Abstract : Objectives: The clinical heterogeneity of frontotemporal dementia (FTD) complicates identification of biomarkers for clinical trials that may be sensitive during the prediagnostic stage. It is not known whether cognitive or behavioural changes during the preclinical period are predictive of genetic status or conversion to clinical FTD. The first objective was to evaluate the most frequent initial symptoms in patients with genetic FTD. The second objective was to evaluate whether preclinical mutation carriers demonstrate unique FTD-related symptoms relative to familial mutation non-carriers. Methods: The current study used data from the Genetic Frontotemporal Dementia Initiative multicentre cohort study collected between 2012 and 2018. Participants included symptomatic carriers (n=185) of a pathogenic mutation in chromosome 9 open reading frame 72 ( C9orf72 ), progranulin ( GRN ) or microtubule-associated protein tau ( MAPT ) and their first-degree biological family members (n=588). Symptom endorsement was documented using informant and clinician-rated scales. Results: The most frequently endorsed initial symptoms among symptomatic patients were apathy (23%), disinhibition (18%), memory impairments (12%), decreased fluency (8%) and impaired articulation (5%). Predominant first symptoms were usually discordant between family members. Relative to biologically related non-carriers, preclinical MAPT carriers endorsed worse mood and sleep symptoms, and C9orf72 carriers endorsed marginally greater abnormal behaviours. Preclinical GRN carriers endorsed less mood symptoms compared with non-carriers, and worse everyday skills. Conclusion: Preclinical mutation carriers exhibited neuropsychiatric symptoms compared with non-carriers that may be considered as future clinical trial outcomes. Given the heterogeneity in symptoms, the detection of clinical transition to symptomatic FTD may be best captured by composite indices integrating the most common initial symptoms for each genetic group.